THE MBKM POLICY AS A STRATEGY TO IMPROVE THE QUALITY OF EDUCATION - Imam Tabroni; Nurarita Nurarita (Lembaga Pengembangan Kinerja Dosen, 2021)
Quality education is education that already has careful planning to improve the quality of human resources, by freeing students from their inability. With the existence of quality education, it will be born a generation that is superior from the aspect of life as the nation's successor. Nadiem Makarim created a new platform, namely “Merdeka Belajar” (Independent Learning), with the latest policies aimed at changing education for the better, improving the quality of human resources in learning and easing the burden that has been borne so far. The method used in this research is descriptive qualitative which aims to describe independent learning as a strategy to improve the quality of education. While the sources taken by the author are scientific books, journals, articles as reference material in this study. The results of the study show that the independent learning policy can ease the burden on students, teachers, schools and the community so that in improving the quality of education the school can focus more and be committed to improving the quality of education.